An investigation of the traditional music session in Ireland's Shannon region - McEntire, Nancy Cassell (Traditiones (Ljubljana), 2012)
Irish traditional music acquisition used to be restricted to specific regions and focused on personal instruction. Now that the individual player is being replaced by larger, lesspersonal groups of musicians, the question of how traditional learning is being accomplished becomes more critical.
Keywords: Etnomuzikologija; ethnomusicology; folk music; folk musik; Ljudska glasba; Ljudske pesmi; folk songs; Ethnopoetics; methodology; Metodologija; Irska; Ireland